The Development of Energy Policy in the European Union: Continuity, Critical Junctures and Change - Versolmann, Ingmar (Routledge/UACES Contemporary European Studies, 2025)
This book uniquely details the longer-term integration of energy policy in the EU, from its inception to the contemporary ‘Energy Union’, whilst also bringing it fully up to date regarding its place in current climate discussions, the European Green Deal, REPowerEU, the European Climate Law and the struggle to achieve net zero. Analysing the policy area from a perspective that explains current developments through economic processes, path dependence, and political decisions over time, the book identifies the factors and mechanisms that enable and constrain actors and energy policy development. It contributes to the broader debate about institutional design and (European) integration in the energy sector, examining key legislation, the motives of actors complying with institutional rules, and the idiosyncratic factors that contribute to continuity and account for change. This book will be of key interest to scholars, students and practitioners/policymakers interested in European energy policy and energy/environmental governance, and more broadly to European politics and theories of European integration, international political economy, public policy, international organisations, and global governance.